2012
DOI: 10.1590/s2179-83972012000100014
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento endovascular dos aneurismas da aorta abdominal com anatomia complexa: resultados preliminares com a segunda geração de endoprótese com arcabouço metálico circular

Abstract: Background: Endovascular treatment has revolutionized the therapeutic approach to abdominal aortic aneurysms due to its low morbidity and mortality rates. Despite technological advances, there are still anatomical limitations to the use of stent grafts. This study aimed to evaluate the immediate clinical results in patients with complex abdominal aortic aneurysms treated with a second-generation stent graft. Methods: This was an observational, prospective, non-randomized, single-centre study with a series of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
2
0
3
Order By: Relevance
“…Contudo, a escolha desta modalidade terapêutica tem sido justificada pela comparação à cirurgia convencional 12 . Bonamigo, Lucas, Junior 13 e Metzer et al 14 estudaram que a prevalência dos aneurismas de aorta pode ser até seis vezes maior nos homens, um percentual próximo ao encontrado no presente estudo.…”
Section: Discussionunclassified
“…Contudo, a escolha desta modalidade terapêutica tem sido justificada pela comparação à cirurgia convencional 12 . Bonamigo, Lucas, Junior 13 e Metzer et al 14 estudaram que a prevalência dos aneurismas de aorta pode ser até seis vezes maior nos homens, um percentual próximo ao encontrado no presente estudo.…”
Section: Discussionunclassified
“…The frequency of hostile anatomy in this patient population can be as high as 50% to 60%. 6,7 In this issue of the Revista Brasileira de Cardiologia Invasiva, Metzger et al 8 reported their experience treating a small group of patients with hostile anatomy, defined by the presence of a strong angulation in the proximal aortic neck or in the emergence of the iliac arteries. In the authors' experience, the use of a device whose characteristics were ideal for this situation produced acceptable success and complication rates.…”
Section: See Page 69mentioning
confidence: 99%
“…These patients must be treated in major reference centres, ideally with the possibility of providing different types of prostheses and complementing the treatment using a percuta neous route when needed, as described by Metzger et al 8 It is also necessary to inform patients of the higher frequency of late leaks and the importance of constant supervision. Acceptable thresholds of success and complications when wider anatomical indication criteria are applied have yet to be defined.…”
Section: See Page 69mentioning
confidence: 99%
“…1,2 Desta forma, há indicação de correção cirúrgica quando o diâmetro for maior que 5,5 cm. 3 Se não tratado, o AAA tem como desfecho sua ruptura iminente, o que provoca mortalidade de 80 a 90% dos casos pela maior taxa de sangramento. 2,4 Atualmente, a maioria das cirurgias de correção são feitas pela via endovascular (EVAR), através do acoplamento de endoprótese no segmento acometido da aorta abdominal.…”
Section: Introductionunclassified
“…A escolha desta técnica predomina por conta da menor mortalidade intra e pós-operatória, além de menor tempo de internação, apesar de possuir maior taxa de reintervenção a longo prazo. 3 Além da escolha da técnica cirúrgica para o tratamento de AAA, vários outros fatores podem influenciar no tempo de internamento e permanência em unidade de terapia intensiva (UTI), como: hipertensão arterial sistêmica, diabetes mellitus, tabagismo, integridade do aneurisma, idade, dentre outros. 5 Embora os dados quanto aos fatores de risco para o desenvolvimento de AAA sejam bem definidos na literatura, os dados relativos ao tempo de internamento, no entanto, são escassos, principalmente se tratando da realidade brasileira.…”
Section: Introductionunclassified